2019
DOI: 10.1074/jbc.ra118.007074
|View full text |Cite
|
Sign up to set email alerts
|

Spatial proteomics reveal that the protein phosphatase PTP1B interacts with and may modify tyrosine phosphorylation of the rhomboid protease RHBDL4

Abstract: Rhomboid-like proteins are evolutionarily conserved, ubiquitous polytopic membrane proteins, including the canonical rhomboid intramembrane serine proteases and also others that have lost protease activity during evolution. We still have much to learn about their cellular roles, and evidence suggests that some may have more than one function. For example, RHBDL4 (rhomboid-like protein 4) is an endoplasmic reticulum (ER)–resident protease that forms a ternary complex with ubiquitinated substrates and p97/VCP (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
(82 reference statements)
4
9
0
Order By: Relevance
“…5d). Significantly, this interaction was also found in our previous large-scale interaction screen of the RHBDL4 interactome -CLIMP-63 aka CKAP4 was one of the reproducible hits in HeLa and HEK 293 cells 49 . We could not detect an interaction between RHBDL4 and RTN4 or ATL1, or between RHBDL4 and CNX, another ER sheet membrane protein (not shown).…”
Section: Rhbdl4 Localises To the Er Sheets And Interacts With Climp-63supporting
confidence: 76%
“…5d). Significantly, this interaction was also found in our previous large-scale interaction screen of the RHBDL4 interactome -CLIMP-63 aka CKAP4 was one of the reproducible hits in HeLa and HEK 293 cells 49 . We could not detect an interaction between RHBDL4 and RTN4 or ATL1, or between RHBDL4 and CNX, another ER sheet membrane protein (not shown).…”
Section: Rhbdl4 Localises To the Er Sheets And Interacts With Climp-63supporting
confidence: 76%
“…Mapping of the cleavage sites revealed that the scissile peptide bonds in L1 and L9 are spaced apart from the TM helix charge, supporting a model that docking and formation of the scission complex are distinct steps. Overall, the emerging picture is that recognition of RHBDL4 substrates is influenced by multiple factors, also including substrate ubiquitination by ERAD E3 ligases (Fleig et al, 2012), integration of signaling from G-protein-coupled receptors (Wunderle et al, 2016), tyrosine phosphorylation of the RHBDL4 cytoplasmic domain (Ikeda and Freeman, 2019) and sensing of the membrane lipid composition (Paschkowsky et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mapping of the cleavage sites revealed that the scissile peptide bonds in L1 and L9 are spaced apart from the TM helix charge, supporting a model that docking and formation of the scission complex are distinct steps. Overall, the emerging picture is that recognition of RHBDL4 substrates is influenced by multiple factors, also including substrate ubiquitination by ERAD E3 ligases (Fleig et al, 2012), integration of signaling from G-protein coupled receptors (Wunderle et al, 2016), tyrosine phosphorylation of the RHBDL4 cytoplasmic domain (Ikeda and Freeman, 2019) and sensing of the membrane lipid composition .…”
Section: Discussionmentioning
confidence: 99%